Accessing globalized health literacy in a multilingual community in the Philippines: A case of cultural appropriation of community-based health services - Faminial, Ilyn Rabago (Animo Repository, 2016)
The study accounted for the appropriated practices in the deployment of health literacy services in multilingual communities. By drawing appropriation construct forwarded by Higgins (2009), health literacy promotions, being contextualized and localized, were further expanded by the views put forth by Canieso-Doronila (1996) and Pennycook (2007).Qualitative multi-sited ethnographic design was employed in the investigation of the access and delivery of health literacy information and services. Participated by health practitioners and recipients from city, municipal and barangay health units, literacy resources, styles of appropriation, and recipients feedback were gathered through interviews and fieldwork observations.By specifically determining culturally and linguistically appropriate health information and services delivered in health facilities, the study found the active use of local languages in the dissemination of literacy initiatives. Moreover, localized resources and contextualized strategies were observed in literacy sessions. With particularized strategies, linguistic and cultural differences were addressed. Adherence to the globally-set standard of literacy was noted, but the recipients seemingly compliant behavior suggested for the creation of locally-favored range of appropriation.